Field notes, February 1, 1978 - Brewer, Marion M.et al (1978)
Field notes for bird sightings submitted by Marion M. Brewer, February 1, 1978. The note mentions the sighting of two Pine Grosbeaks, as well as six Short-eared Owls; the latter were seen south of Cherokee. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter, 1977-1978. Epson - sheet feed/flatbed